Pelatihan Kolaborasi Guru dan Orang Tua Anak Disabilitas dalam Pelaksanaan Program Pembelajaran Individu (PPI) - Widya Rini Setyaningsih; Emiliana Syahdariani; Cahyaning Suryaningrum; Yuni Nurhamida (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
Collaboration between teachers and parents plays an important role in the successful implementation of Individualized Education Programs (IEPs) for children with disabilities. However, IEP implementation still faces several challenges, including inconsistent communication, differences in perceptions regarding children’s needs, and limited understanding of appropriate learning strategies. Preliminary observations conducted at Al-Firdaus Cahaya Inklusi School in Malang revealed that teachers and parents did not yet have a structured collaborative forum for planning and implementing IEPs. This activity aimed to improve teachers’ and parents’ understanding and collaborative skills in implementing Individualized Education Programs through a collaborative training program. The study employed a one-group pretest-posttest design using a mixed-methods approach. The participants consisted of 20 individuals, including 10 teachers and 10 parents of children with disabilities. Quantitative data were collected through pretests and posttests, while qualitative data were obtained through direct observation during the training activities. The results showed an average improvement of 30% in participants’ scores. The highest increase was found in understanding collaboration concepts in IEP implementation (40%), followed by collaborative skills (35%) and understanding the characteristics of children with disabilities (15%). Observation findings also indicated that teachers and parents were able to collaboratively identify children’s needs, formulate learning objectives, and agree on program implementation strategies. Therefore, the collaborative training program was effective in improving teacher-parent collaboration in the implementation of Individualized Education Programs for children with disabilities.